China’s Belt Road Initiative: Dalam Pandangan Teori Geopolitik Klasik - Iqbal Ramadhan (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2018)
This article aims to examine the issue of China's Belt Road Initiative (BRI) in the view of classical geopolitical theory. The theory basically appeared in the 19th century. The classical geopolitical theory used in this article is McKinder Theory and Mahan Theory. Nevertheless, the theory is still relevant enough to answer China's policy as well as what geopolitical advantages the country gains. By using qualitative research, classical geopolitical theory was used to examine China's BRI policy on the construction of terrestrial trade corridor passes through Eurasia region and maritime silk road which cross strategic waterway. This article concludes that when the project is implemented, China will not only benefit economically but also be able to change the geopolitical constellation of the world. Although it is still too early, the BRI project has the potential to make China as the next superpower.